Intelligent irrigation control in olive groves (Olea europaea L.): A novel approach for water resource optimization - Vita Serman, Alberto Facundo (2012)
In the last years, irrigation control in agricultural soils has been mainly focused on the optimization of the use of water resources, in order to overcome the difficulties imposed by a growing water demand and to reduce extraction costs. This work presents the field implementation of an automatic irrigation controller, as a novel approach for water resource optimization.The developed closed-loop irrigation control system includes the moisture measurement in roots zone and the control of the irrigation valves in order to maintain the moisture level around a set value.The controller determines when and how much to irrigate as a function of the current difference between soil moisture measurements and the reference values.The system is used in three irrigation treatments with different set-point moisture level: T1: soil moisture at field capacity; T2: water deficit level from pit hardening to harvest (40% of field capacity); and T3: water deficit level from fruit set to harvest (40% of field capacity).Experiences were carried out in a four-year-old experimental olive orchard grown "Arbequina", located in San Juan, Argentina.Controller was able to maintain soil moisture values around the reference value, fact that allow performing different irrigation strategies. Productive and qualitative parameters were affected by applying water deficit treatments in different phenological moments, being specially affected the obtained oil quality.